2021
DOI: 10.3390/ijms22062910
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of MicroRNAs in Male Infertility

Abstract: MicroRNAs applications were vastly studied throughout the years, spanning from potential cancer biomarkers to targeted therapies for various diseases. Out of these utilizations, this paper focuses on their role in male infertility. Approximately 10–15% of worldwide couples are affected by infertility. Out of these, 50% are due to male determinants. The majority of cases still have an undetermined cause. Previous studies have found that the aberrant expression of microRNAs could be linked to certain reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 113 publications
0
38
0
Order By: Relevance
“…Some studies suggested that miRNAs might also be involved in male infertility (Khazaie & Nasr Esfahani, 2014). Some differentially expressed miRNAs in this research, such as miR-34c-5p, miR-34b-5p, miR-146b-5p, miR-449a and miR-765, were reported that could potentially be used as diagnostic biomarkers for idiopathic male infertility (Barbu et al, 2021), as well as in the development of innovative targeted therapeutic tools. Athenozoospermia is a common cause of male infertility.…”
Section: Functional Enrichment Analysis Of Target Genes Of Differenti...mentioning
confidence: 73%
“…Some studies suggested that miRNAs might also be involved in male infertility (Khazaie & Nasr Esfahani, 2014). Some differentially expressed miRNAs in this research, such as miR-34c-5p, miR-34b-5p, miR-146b-5p, miR-449a and miR-765, were reported that could potentially be used as diagnostic biomarkers for idiopathic male infertility (Barbu et al, 2021), as well as in the development of innovative targeted therapeutic tools. Athenozoospermia is a common cause of male infertility.…”
Section: Functional Enrichment Analysis Of Target Genes Of Differenti...mentioning
confidence: 73%
“…Sperm sRNA profiles, especially alterations in miRNA have been studied in infertile men (Abu-Halima et al, 2014;Lian et al, 2009;Muñoz, Mata, Bassas, & Larriba, 2015;Salas-Huetos et al, 2016b;C. Wang et al, 2011), and have been suggested as biomarkers of male infertility (Kotaja, 2014;Barbu et al, 2021;Kiani, Salehi, & Mogheiseh, 2019;Salas-Huetos et al, 2020). Additionally, sperm tsRNA, miRNA and rsRNA has recently been shown to correlate with embryo quality (Grosso et al, 2021;Hua et al, 2019;Nätt & Öst, 2020; and piRNA are involved in paternal diet induced intergenerational response (Lempradl et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…1 Globally, about 10% to 15% of couples are affected by various conditions that lead to infertility, with up to 50% of those affected by male factors. 1,2 More than 30 million people worldwide suffer from male infertility. 3 Male infertility not only causes psychological pain to families but also increases certain economic burdens faced by society.…”
Section: Introductionmentioning
confidence: 99%